Huntingtin-associated protein 1 ameliorates neurological function rehabilitation by facilitating neurite elongation through TrKA-MAPK pathway in mice spinal cord injury - Miao, Li; Qing, Sun Wan; Tao, Lu (Frontiers in Molecular Neuroscience, 2023)
Aims: Huntingtin-associated protein 1 (HAP1) is a neuronal protein closely associated with microtubules and might facilitate neurological function rehabilitation. This study aimed to investigate the effects of HAP1 on SCI and the underlying mechanisms.Methods: the spinal cord injury (SCI) mouse model was induced by Allen's method. Then recombinant-HAP1 (r-HAP1) was administrated by intrathecal injection, and the BMS, Thermal nociceptive thresholds, tactile nociceptive thresholds, and neurofibrillary regeneration were identified to inspect the therapy outcome. Then NSCs were isolated from mice on embryonic day 14.5 and induced to differentiate into neurons. The efficiency of axon growth was calculated. Signaling pathway array was conducted to examine the signaling pathways in NSCs treated with r-HAP1. Antagonists and activators of TrkA were used to confirm the role of TrkA of HAP1 intervention both in vitro and in vivo. Results: r-HAP1 ameliorates the neurological function rehabilitation after SCI, and benefits the regain of Tuj in injury spinal cord. Also significantly enhances neurite growth during neuronal differentiation of NSCs; Signaling pathway array and Western blot revealed that r-HAP1 significantly activates the phosphorylation of TrkA-MAPK/ERK in NSCs. TrkA selective inhibitor GW441756 blocks r-HAP1 on TrkA-MAPK/ERK signaling pathway and detracts from axonal growth after neuronal differentiation. TrkA selective activator gambogic amide can mimic the HAP1 facilitated SCI rehabilitation 2 function of r-HAP1 by activating the foregoing pathway. ERK activator U-46619 reverses the blocking effect of GW441756 on r-HAP1. Conclusion: HAP1 activates the TrkA-MAPK signaling pathway and is conducive to neurite elongation during NSC neuronal differentiation; by which to improve the prognosis of spinal cord